Квантовый выход межзонной излучательной рекомбинации в кристаллах CdHgTe - Vlasenko, A. I.; Vlasenko, Z. K. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
A calculation of the quantum efficiency of interband radiative recombination in CdHgTe crystals is carried out, taking into account their composition, doping level, temperature, and optical excitation level. It is shown that an increase in quantum efficiency of radiative recombination in the interband process in both n- and p-type crystals across the entire doping range is achieved by lowering the temperature and increasing the band gap width. In p-type crystals, doping with acceptor defects within certain limits, depending on the material composition, also contributes to higher quantum efficiency.